ANALISIS POTENSI WISATA DAN PARTISIPASI MASYARAKAT UNTUK ARAHAN PENGEMBANGAN DESA WISATA PURBOSARI KECAMATAN NGADIREJO KABUPATEN TEMANGGUNG TAHUN 2023 - Kaltsum Hana Arini; Chatarina Muryani; Rahning Utomowati (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
Tourism is currently not only concentrated in big cities, but has spread to rural areas due to its dynamic growth. This is a form of accelerating village development which aims to encourage social, cultural and economic change in rural areas. Therefore, each region or village must look at the potential of its region to be improved in order to produce added value benefits and high productivity. This research aims to determine tourism potential, community participation, and appropriate development directions for the Purbosari Tourism Village, Ngadirejo District, Temanggung Regency. Measuring tourism potential using the scoring method, community participation using the Arnstein participation ladder with the Miles-Huberman interactive model, and determining the direction of tourism village development using the SAST method. The analysis technique used is descriptive qualitative using a case study approach. The results of this research show that the Purbosari Tourism Village has three types of tourism potential levels, namely low, medium and high. Community participation in Purbosari Village has a low level of participation/non-participation with the therapy/therapy participation category for the planning and implementation stages and a moderate level of participation/tokenism with the placement/placation participation category for the monitoring and evaluation stages. The SAST method produces 20 stakeholder assumptions for the direction of developing tourist villages in quadrants II, III and IV.